Knowledge sharing behavior among academic staff of Universiti Teknologi Tun Hussien Onn / Nazarudin Derasid - Derasid, Nazarudin (2014)
This study was about to identify the relationship of knowledge sharing behavior among academic staffs of Universiti Teknologi Tun Hussien Onn. The main objective of this study is four. First, the study was to examine the relationship between attitude with knowledge sharing behavior. Second, it was to determine the relationship between leadership and knowledge sharing behaviour. Third, was to find out the relationship between reward system and knowledge sharing behavior.Fourth, to determine the relationship between knowledge sharing system and knowledge sharing behaviour.A total of 250 questionnaires were distributed to academic staffs from eight (8) academic faculties which are Faculty of Civil Engineering,Faculty of Mechanical Engineering, Faculty of Electrical Engineering, Faculty of Technology Management & Business, Faculty of Computer Science & Information Technology, Faculty of Technical & Vocational Education, Faculty of Science, Technology & Human Development and Faculty of Engineering Technology. However, only 227 were returned and usable for analysis. Pearson Correlation analysis was performed to tests the relationship between the variable. The results indicated that of the four (4) components of variable were significant to the knowledge sharing behaviour. The findings were discussed and recommendations for the future research were also addressed.